The Pontryagin maximum principle for solving Fokker–Planck optimal control problems - Tim Breitenbach; Alfio Borzì (Computational Optimization and Applications, 2020)
The characterization and numerical solution of two non-smooth optimal control problems governed by a Fokker–Planck (FP) equation are investigated in the framework of the Pontryagin maximum principle (PMP). The two FP control problems are related to the problem of determining open- and closed-loop controls for a stochastic process whose probability density function is modelled by the FP equation. In both cases, existence and PMP characterisation of optimal controls are proved, and PMP-based numerical optimization schemes are implemented that solve the PMP optimality conditions to determine the controls sought. Results of experiments are presented that successfully validate the proposed computational framework and allow to compare the two control strategies.
Keywords: Q84; J20; E20; M05; 510; Fokker–Planck equation; Pontryagin maximum principle; Non-smooth optimal control problems; Stochastic processes